Prostaglandin E(2) receptor 3 signaling is induced in placentas with unexplained recurrent pregnancy losses - Ye, Yao (Endocr Connect, 2018)
Although an inflammatory microenvironment is required for successful implantation, an inflammatory overreaction is one of the causes of unexplained recurrent pregnancy losses (uRPL). Prostaglandin E(2) (PGE(2)) plays a pivotal role in regulating immune balance during early pregnancy, and it can stimulate inflammatory reactions via prostaglandin E(2) receptor 3 (EP3). However, the role of PGE(2) receptor signaling in the uRPL remains unknown. We aimed to investigate whether EP3 signaling is involved in the mechanism of uRPL. Via immunohistochemistry we could show that the expression of cyclooxygenase-2, EP3 and G protein alpha inhibitor 1 (G(i1)) was enhanced in the decidua of the uRPL group in comparison to the control group in first-trimester placentas. In vitro, we demonstrated that sulprostone (an EP1/EP3 agonist) inhibited the secretion of beta-hCG and progesterone in JEG-3 cells and the secretion of beta-hCG in HTR-8/SVneo cells while it induced the expression of plasminogen activator inhibitor type 1 in JEG-3 cells. In addition, PGE(2)/sulprostone was able to stimulate the expression of G(i1), phosphorylated-extracellular signal-regulated kinases 1/2 (p-ERK1/2) and p53. L-798,106 (an EP3-specific antagonist) suppressed the expression of EP3 and p-ERK1/2 without affecting the secretion of beta-hCG. Elevated activation of EP3 signaling in first-trimester placentas plays an important role in regulating the inflammatory microenvironment, the hormone secretion of extravillous trophoblasts and the remodeling of extracellular matrix in the fetal-maternal interface. L-798,106 might be a ‘potential therapeutic candidate’ for the treatment of uRPL.